A systematic review of health education theories and approaches in improving the oral health behaviour among adults - Manoranjitha, B. S.; K. M., Shwetha; Pushpanjali, K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Theoretical models analysing patient behaviour are necessary to understand the complex relationships underlying human behaviour. The widely accepted definition of health is according to World Health Organization (WHO) “a state of complete physical, mental and social wellbeing, not merely an absence of disease or infirmity.” To assess effectiveness of theory and approaches of oral health education in changing the oral health behaviour and improving the oral hygiene status among adults. Methods: PubMed database was searched for published studies in English language. The search dates were limited to 1990 onwards, applied to the inclusion criteria. Primary outcome was the change in oral hygiene behaviour, measured by self-reported and observed measures. Secondary outcomes were changes in plaque score, dental knowledge. Relevant titles and abstracts of studies were screened. Quality assessment was done for the studies included using checklist of items for randomized controlled trail. (CONSORT) These studies were categorised based on the type of theory used, type of intervention and outcome. Results: Out of 48 studies obtained based on the title and abstract, 15 studies were excluded based on inclusion and exclusion criteria. 13 studies fulfilled the inclusion. These studies were categorised based on the type of theory used. Studies based on 1) Operant and Classical conditioning theory 2) Social cognitive theory. 3) Self-efficacy model. 3) Transtheoritical model. 4) Motivational interviewing. 5) Self-regulatory model. 6) Health action process approach. 7) Implementation intention theory. Conclusions: Theory and approach based oral health education is effective in significantly improving the oral hygiene behaviour.